A systematic mapping review of augmented reality applications to support STEM learning in higher education - Mystakidis, Stylianos; Christopoulos, Athanasios; Pellas, Nikolaos (Education and information technologies, 2022)
While there is an increasing interest in Augmented Reality (AR) technologies in Primary and Secondary (K-12) Education, its application in Higher Education (HE) is still an emerging trend. This study reports findings from a systematic mapping review, based on a total of forty-five ( n = 45) articles published in international peer-reviewed journals from 2010 to 2020, after evaluating the use of AR applications that support Science, Technology, Engineering and Mathematics (STEM) subjects’ learning in HE settings. This review’s results highlighted the lack of research across the STEM spectrum, especially in the Technology and Mathematics subfields, as well as the scarcity of location-based and markerless AR applications. Furthermore, three augmentation techniques, suitable for STEM learning, were identified and analysed: augmentation of laboratory specialised equipment, physical objects and course handbooks or sheets. The main contribution of this article is a taxonomy of instructional models and the discussion of applied instructional strategies and techniques in STEM fields focused on HE settings. In addition, we provide visualisations of the present state of the area, which aim at encouraging and scaffolding educators’ efforts based on specific classification criteria to develop AR experiences and conduct further research to enhance STEM learning.